DETERMINATION OF PROFESSIONAL IDENTITY OF SECOND SCHOOL’S STUDENTS - Pshuk, Nataliya; Pototska, Iryna (PSYCHOLOGICAL JOURNAL, 2016)
The article describes the relevance of the research status of modern professional school students. Identifies authors who study this issue in the present conditions change and reform of modern education system. Empirical research using the test was John. Marcia «The definition of professional status», which identifies the following professional status «uncertain professional identity», «imposed on professional identity (won)», «moratorium (the crisis of choice) professional identity» and «Formed professional identity». The survey results show that nearly half manifests a modern high school professional status as a «moratorium» crisis characterized by the choice of profession, uncertainty and the search for alternatives. It describes the reasons for the existence of just such a status. The next most detected status is «acquired identity» as a result of the influence of parents and entourage for a decision on his future profession. Next in importance is «uncertain identity». These high school students still do not know who would like to be like their skills and abilities could be used in future activities. Only a very small number of senior professional identity manifested formed, indicating a clear vision of their future and will manifest as high motivation in teaching in higher education.